PENANAMAN NILAI-NILAI MU’ASYAROH BIL MA’RUF DALAM MEMBANGUN KELUARGA BAHAGIA DI ERA DIGITAL - Abdurrahman zanky (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
The digital era presents significant challenges for family life, particularly in maintaining harmonious relationships among family members. The influence of technology, social media, and digital lifestyles often disrupts the quality of direct interactions and worsens family communication. This article discusses the application of the values of mu'asyaroh bil ma'ruf in building a happy family amidst digital developments. The main focus is on strategies for instilling values, including digital time management, active communication, and spiritual development. By applying Islamic values that emphasize love, justice, and mutual respect, families can overcome the challenges posed by the digital world. It is hoped that families can find a balance between digital life and togetherness within the household, leading to long-lasting harmony and happiness.